Conditioning intensity in secondary AML with prior myelodysplastic syndrome/myeloproliferative disorders: an EBMT ALWP study - Sengsayadeth, Salyka; Dreger, Peter (Blood advances, 2018)
Patients with secondary AML (sAML) with antecedent myelodysplastic syndrome (MDS) or myeloproliferative neoplasms (MPNs) tend to have high-risk disease based on the older age of patients, high-risk cytogenetics, and higher number of prior treatments. Allogeneic hematopoietic cell transplant (HCT) is the only potentially curative therapy available. Eight hundred and two adults with sAML and prior MDS/MPN who received a first HCT between 2000 and 2016 were included in the European Society for Blood and Marrow Transplant (EBMT) Acute Leukemia Working Party (ALWP) study. Median age of the cohort was 59.6 years (range, 18.6-78.6 years). Myeloablative conditioning (MAC) was given to 40% of patients, and 60% received reduced-intensity conditioning (RIC). Overall, the 2-year cumulative incidence of relapse (RI) was 37%, leukemia-free survival (LFS) was 40%, overall survival (OS) was 46%, nonrelapse mortality (NRM) was 23%, and chronic graft-versus-host disease (cGVHD) was 39%. In univariate analysis, a statistical difference between conditioning regimens 6 months after HCT in favor of the MAC group was noted with regard to RI (hazard ratio [HR], 1.47; P = .03), LFS (HR, 1.43; P = .01), and OS (HR, 1.55; P < .05). There was no difference in the cumulative incidence of NRM (HR, 1.38; P = .15). This effect was similarly seen in multivariate analysis (MVA): cumulative incidence of relapse (HR, 1.79; P < .05), LFS (HR, 1.43; P = .02), and OS (HR, 1.53; P = .005) with no difference in NRM (HR, 1; P = .98). This EBMT ALWP analysis suggests that long-term survival can be achieved in patients with sAML with antecedent MDS/MPN and that MAC is a suitable conditioning regimen in patients with sAML.
Gesehen am 30.09.2019